2021
DOI: 10.1016/j.isci.2021.102357
|View full text |Cite
|
Sign up to set email alerts
|

Cryopreservation of microglia enables single-cell RNA sequencing with minimal effects on disease-related gene expression patterns

Abstract: Summary Microglia play a key role in brain development, normal homeostasis, and neurodegenerative disorders. Single-cell technologies have led to important findings about microglia, with many animal model studies using single-cell RNA sequencing (scRNA-seq), whereas most human specimen studies using archived frozen brains for single-nucleus RNA sequencing (snRNA-seq). However, microglia compose a small proportion of the total brain tissue; snRNAseq depletes expression of microglia activation genes t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 56 publications
0
26
0
Order By: Relevance
“…At necropsy, blood-borne cells were cleared by perfusion with PBS containing 1U/mL heparin. Microglia/macrophage-enriched cellular isolation from the brain was performed using our previously described procedure of physical and enzymatic disassociation followed by Ficoll gradient purification (10, 137), and then cryopreserved in the presence of 10% DMSO / 90% fetal bovine serum and stored over liquid nitrogen. Brain regions were dissected by a board-certified pathologist, frozen, and stored at −80° C.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…At necropsy, blood-borne cells were cleared by perfusion with PBS containing 1U/mL heparin. Microglia/macrophage-enriched cellular isolation from the brain was performed using our previously described procedure of physical and enzymatic disassociation followed by Ficoll gradient purification (10, 137), and then cryopreserved in the presence of 10% DMSO / 90% fetal bovine serum and stored over liquid nitrogen. Brain regions were dissected by a board-certified pathologist, frozen, and stored at −80° C.…”
Section: Methodsmentioning
confidence: 99%
“…scRNA-seq procedures were completed using our previously described methods (137, 142). Briefly, cryopreserved microglia were treated with 1% DNase (Sigma Aldrich), washed, stained with UV-blue live/dead assay (Invitrogen, Waltham, MA).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have demonstrated that exposing mammalian cells to sub-physiological temperatures invokes a coordinated cellular response involving induction of cold-shock proteins and modulation of translation, metabolism, cell cycle and the cell cytoskeleton [39]. Therefore, although cold digestion prevents, to a large extent, the dissociation-induced artefacts, it is still possible to alter in some way the in vivo molecular profile of the cells, for example, cryopreserved cells experiment some induction of earlyresponse genes [40]. Of note, cells isolated using standard procedures also commonly experience cold-stress during several steps of the protocol, such as centrifugation and transfer of cells, as these steps are performed at 4°C and on ice, respectively.…”
Section: Cell Dissociation With Cold Active Proteasesmentioning
confidence: 99%
“…While total transcript can be extracted from archival tissue using single-nuclei RNA-seq, detecting activation of state-associated genes is inconsistent between brain studies. On one hand, disease-activated genes were preserved in frozen microglial nuclei 24,25 . However, a meta-analysis of publicly available microglial datasets indicates that microglial activation genes may be depleted in single-nuclei RNA-seq datasets, including genes involved in AD 26 .…”
Section: Introductionmentioning
confidence: 99%